Pendampingan Penyusunan Laporan Keuangan sesuai Standar Akuntansi bagi Pelaku UMKM di Jatiluhur Bekasi - Ria, Ria; Digdowiseiso, Kumba (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
In general, not all MSMEs are able to prepare financial reports in running their business. On the one hand, company owners want financial statements as a condition for bank credit. The purpose of this service is to provide an understanding of the preparation of financial reports according to accounting standards for MSMEs in Jatiluhur District, Bekasi City. The service method used is Asset Based Community Development (ABCD) through training. The dedication team empowers existing assets in the Jaliluhur Village, especially in managing their financial reports better and more accurately. The results of the dedication are that the Micro, Small and Medium Enterprises (MSMEs) in Jatiluhur District, Bekasi City, have not been fully optimal in the use and preparation of financial reports. The results of the training show that many participants initially had limitations in their ability to prepare financial reports properly and correctly. Therefore, continuous assistance and guidance is needed to improve their quality and understanding regarding financial aspects.